Gatti, N & Ossum-Batsa, G, Bern: Peter Lang. (Das Alte Testament im Dialog vol 5) - S. D. Snyman (Acta Theologica)
From text: This book is the result of many years of teaching the Old Testament in Africa especially in the country of Ghana at two Ghanese universities. The aim of the book is to provide the student/reader with a general introductory study of the Old Testament. The intended audience of the book is clearly students with questions put and exercises recommended to see whether the work has been mastered in a sufficient way.